Dinâmica e composição da matriz energética industrial brasileira: análise atual e cenários prospectivos - Pinto, Vítor Guedes (Universidade Federal de São Carlos, 2025)
The Brazilian industrial energy matrix has undergone significant transformations in recent years, driven by economic crises, technological advancements, and public policies. This work critically analyzes this evolution, investigating changes in the share of renewable (hydropower, biomass, wind) and non-renewable (natural gas, coal) energy sources in the industrial sector, as well as the political, socioeconomic, and technological factors that determined them. The methodology combines a systematic literature review of indexed scientific articles (Scopus, SciELO) and sectoral reports (EPE, ANEEL, MME) with quantitative analysis of energy data. The results reveal that, despite the significant share of renewable sources such as sugarcane bagasse and hydroelectric power, challenges like water seasonality and regional dependence persist. The study also highlights the potential of emerging alternatives including biogas, green hydrogen, and solar thermal energy, whose development requires research investments and coordinated policies to ensure industrial growth aligned with environmental sustainability.
Dynamics and composition of the brazilian industrial energy matrix: current analysis and prospective scenarios
Keywords: Matriz energética; Matriz industrial; Energias renováveis; Energy matrix; Industrial matrix; Renewable energy; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA